EXPERIENCIAS EXITOSAS EN REDES TEMÁTICAS DE DOCENCIA IBEROAMERICANAS EN LA FACULTAD DE CIENCIAS ADMINISTRATIVAS - Fairlie Frisancho, Ebor (2009)
This article aims to inform the academic community of Administrative Sciences Faculty, the importance of belonging and shape Subject Teaching Networks with the successful completion of two thematic networks; Tourism and Development and the Environment, formed in 2007 between the Corporación Universitaria del Meta (Colombia), Universidad de Panamá (Panamá) and the Universidad Nacional Mayor de San Marcos (Perú) with the implementation of four International Conferences with professors from these universities who traveled fully supported with aid provided by the Group of Latin American Universities of La Rabida, sponsored by Universidad Internacional de Andalucía (España) and the issue of Proceedings of the conference, including the publication of each paper.